Pengembangan Media DISMENORYBOOK (Dismenorea Diary Book) Mengenai Pencegahan Dismenorea pada Remaja Putri Kabupaten Subang (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Dysmenorrhea in adolescent girls is one of the problems that results in disruption of activities of daily activities. After the researchers conducted a preliminary study using interview techniques with young women in Nagrak Village, Ciater District, Subang Regency, it was found that nine out of ten young women experienced dysmenorrhea, which means 90% of young women experienced dysmenorrhea. Purpose: Develop and assess the feasibility of the DismenoryBook (Dysmenorrhea Diary Book) media regarding the prevention of dysmenorrhea in adolescent girls. Methods: This research is a type of development (Research and Development) using the PPE development model (Planning, Production, and Evaluation). The number of samples is 37 young women using purposive sampling technique. Result: The feasibility of the media was 84%, the feasibility of the material was 83.6% and the feasibility of the media to young female users was 92.5%. Conclusion: The assessment of the feasibility of the DismenoryBook (Dismenorea Diary Book) by material experts, media experts, and users got the results